HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN WANITA MENOPAUSE - La Ode Alifariki (Poltekkes Kemenkes Jambi, 2023)
Background. Menopause is the time when a woman's menstrual period and her ability to bear children stop permanently. Women who have gone through menopause are prone to anxiety and stress with the conditions they experience.. This study aims to determine the correlation between the level knowledge, husband's social support with anxiety level of menopausal women in ​​the Lepo Lepo Health Center work area, Kendari City. Methods. This cross-sectional study was conducted in the working area of the Lepo-Lepo Health Center with a sample of 65 women aged >45 years. The sample was taken using a purposive sampling technique. Data was collected using primary data in the form of a questionnaire that was in accordance with the inclusion criteria. The data were processed using the Chi-square statistical test. Results. Statistical test results found on the variable level of anxiety showed that out of 65 respondents who suffered from anxiety more, namely 44 respondents (67.7%) and those who did not suffer from anxiety as many as 21 respondents (32.3%) from the results obtained there was a significant relationship between the level knowledge, husband's social support with anxiety level of menopausal women (p=0.008). Conclusion. The conclusion of this study is that there is a correlation the level knowledge, husband's social support with anxiety level of menopausal women in ​​the Lepo Lepo Health Center work area, Kendari City.